2004
DOI: 10.1007/s10464-004-7415-3
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Perceptions of Neighborhood Characteristics and Substance Use Among Urban African American Adolescents

Abstract: Although the neighborhood microsystem is recognized as an important domain for adolescent development, relative to the family and peer contexts, neighborhood factors have been understudied in relation to adolescent substance abuse. In addition, recent research suggests that risk factors for adolescent substance use may differ for African Americans when compared to Caucasian youth. This study investigated the association between perceived neighborhood disorganization and later substance use, as well as possible… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
170
2
8

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 200 publications
(188 citation statements)
references
References 52 publications
8
170
2
8
Order By: Relevance
“…Perceived level of neighborhood safety also seems associated with lower risk for substanceuse disorders. This finding is consistent with other research (Cho, Park, & Echevarria-Cruz, 2005;Lambert, Brown, Phillips, & Ialongo, 2004;Wandersman & Nation, 1998) which emphasizes the importance of the receiving context, particularly early exposure to neighborhood disadvantage as a risk factor for illness, even after controlling for individuallevel socioeconomic status. For substance-use disorders, the importance of arrival to the U.S. after age 25 offers insight into the context-dependent risk for substance use disorders.…”
Section: Discussionsupporting
confidence: 92%
“…Perceived level of neighborhood safety also seems associated with lower risk for substanceuse disorders. This finding is consistent with other research (Cho, Park, & Echevarria-Cruz, 2005;Lambert, Brown, Phillips, & Ialongo, 2004;Wandersman & Nation, 1998) which emphasizes the importance of the receiving context, particularly early exposure to neighborhood disadvantage as a risk factor for illness, even after controlling for individuallevel socioeconomic status. For substance-use disorders, the importance of arrival to the U.S. after age 25 offers insight into the context-dependent risk for substance use disorders.…”
Section: Discussionsupporting
confidence: 92%
“…In a community sample of urban African Americans in Baltimore city, perceptions of neighborhood disorder in 7th grade were associated with 9th grade drug use (defined as alcohol, tobacco, or marijuana use). 15 In this same sample but not restricted to African Americans, youth living in neighborhoods with an increasing presence of abandoned buildings over time were more likely to use marijuana 2 years after high school compared to youth living in "always-good" neighborhoods. 16 More recently, in a small study of young adult African American men in Chicago, those reporting high levels of neighborhood disorder were more likely to report a history of marijuana use.…”
Section: Introductionmentioning
confidence: 87%
“…Lambert et al (2004) found that perceived neighborhood disorder (e.g., drug sales and violent crimes) in Grade 7 was associated with increased marijuana use in Grade 9 using a sample of African American youth in the city of Baltimore. A similar linkage was discovered between perceived neighborhood disorder and current marijuana use among middle-school students from three different states in the United States (Wilson et al, 2005).…”
Section: Theoretical Frameworkmentioning
confidence: 97%
“…There is a growing body of work substantiating the association between neighborhood disorder and adolescent and young adult marijuana use (Burlew et al, 2009;Lambert et al, 2004;Reboussin et al, 2007;Theall et al, 2009;Wilson et al, 2005). Lambert et al (2004) found that perceived neighborhood disorder (e.g., drug sales and violent crimes) in Grade 7 was associated with increased marijuana use in Grade 9 using a sample of African American youth in the city of Baltimore.…”
Section: Theoretical Frameworkmentioning
confidence: 99%